The Wider Impacts of Universities: Habermas on Learning Processes and Universities - Jesper Eckhardt Larsen (Nordicum-Mediterraneum, 2013)
The discourse of reform in higher education tends to focus narrowly on employability and the relationship between higher education and the labor market. Universities as research institutions are now considered solely in the dominant discourse of innovation. This way of conceiving universities is inspired by functionalist theory that focuses on the imperatives of a knowledge economy. Taking a departure in the theory of society developed by Jürgen Habermas this paper seeks to provide a theoretical framework for an empirical comparative analysis on the wider societal impact of universities. It is the argument that the wider impacts of higher education and research at universities must be seen in a more complex vision of modern societies. The paper is thus primarily a re-reading of Habermas’ critique of functionalist views of the university and an application of Habermas’ critique on current issues in the debates on higher education. A special discussion will be taken on issues of the self in view of the current tendencies to regard all education from the standpoint of the economic outputs.